THE EFFECT OF TIKTOK EFFECTIVENESS AND PEER INFLUENCE ON CONSUMPTION BEHAVIOR WITH FINANCIAL LITERACY AS A MEDIATOR AMONG GENERATION Z IN JAKARTA - Tantri Auliya; Suparno; Aditya Pratama (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The rise of social media platforms like TikTok has significantly influenced Generation Z's consumption patterns, yet the mediating role of financial literacy remains unclear. This study examines the influence of TikTok effectiveness and peer groups on consumptive behavior, with financial literacy as a mediating variable among Generation Z in Jakarta. Using PLS-SEM analysis with 150 respondents, the findings reveal that TikTok effectiveness (β=0.382) and peer groups (β=0.452) both positively and significantly affect consumptive behavior. Financial literacy negatively influences consumptive behavior but does not significantly mediate the relationships. However, both TikTok effectiveness and peer groups positively influence financial literacy. These results highlight the dominant role of social media and peer environments in driving Gen Z's consumption patterns, while revealing limited mediating capacity of financial literacy. The study suggests developing engaging financial education content on social media platforms and peer-based financial awareness programs to promote responsible consumption among young consumers.